PENGUJIAN SENSORIS NUGGET AYAM FORTIFIKASI DAUN KELOR - Sri Hastuti; Sinar Suryawati; Iffan Maflahah (Agroindustrial Technology, University of Trunojoyo Madura, 2015)
Innovation chicken nuggets with fortification Moringa leaves can be expected as a source of protein as well as of other nutritional components needed by the body. Sensory testing nugget products have been set by the National Standardization Agency (BSN) is SNI No. 2346: 2011. The purpose of this study was to determine sensory and preference of chicken nuggets with fresh Moringa leaves and moringa leaf powder 2% fortification. The results showed that the sensory testing of the appearance, smell, taste and texture nuggets still appropriate ISO standard that is above 7. While testing of the texture, taste, color and odor generating value from moderate like to like.